MUMTOZ ADABIYOTDA KO‘NGIL TIMSOLI TASVIRIDA AN’ANA VA O‘ZIGA XOSLIK (Bobur lirikasi misolida) - Qahharova, D.A. (SCIENCE and SOCIETY, 2023)
The article refers to the sybol of the heart, which is widely used in classical literature. The interpretation of the sybol of the soul in different places in the work of representatives of classic literature is analyzed with the help of examples. Also, the meaning of the use of the image of the heart in Babur’s lyrics is analyzed by giving examples from the poet’s ghazals and rubai.